Seroprevalence and risk factors associated with Neospora caninum in commercial sheep from northwest of Rio Grande do Sul, Brazil - Consalter, Angélica; Silva, Andressa Ferreira da; Gaia, Vinicius Grangeia; Zanella, Eraldo Lourenso; Souza, Guilherme Nunes de; Ferreira, Ana Maria Reis (Semina: Ciências Agrárias, 2020)
Neospora caninum is a widely distributed parasite, which significantly impacts reproduction in ruminants. This study aimed to survey the seroprevalence and risk factors associated with neosporosis infection in commercial herds of sheep in the northwest of Rio Grande do Sul, Brazil. Three hundred sheep serum samples were used to investigate anti-N. caninum antibodies using indirect immunofluorescence reaction at a 1:40 dilution. The presence of anti-N. caninum antibodies was detected in 20.3% (61/300) of the samples evaluated; however, positive reactions were observed in all (13/13) flocks sampled. Sheep breeds > 1 year of age had 1.2-fold higher risk for infection with N. caninum (odds ratio 2.2 [95% confidence interval 1-5.1]; P < 0.001). These findings should raise awareness on the importance of serological screening, identification of risk factors, and maintenance of preventive measures, such as not allowing dogs to contact sheep feed and not offering the placental remains of ruminants to canids.